Autoclave and ultra-sonication treatments of oil palm empty fruit bunch fibers for cellulose extraction and its polypropylene composite properties - Abdullah, M.A. (Elsevier Ltd, 2016)
Accumulation of residual plastics and the biomass wastes from agricultural sectors are causing serious global environmental problems if not addressed effectively. Cellulose with polypropylene as biocomposite material is an elegant strategy for value-added utilization of wastes. In this study, green isolation of cellulose from oil palm empty fruit bunches by autoclave-based and ultrasonication pre-treatments were developed to replace the non-green chlorite method. Ultrasonic treatment with hydrogen peroxide yielded 49 cellulose with 91.3 Î±-cellulose content and 68.7 crystallinity, as compared to 64 cellulose with autoclave treatment. Based on field emission scanning electron microscope, the ultrasonic and the autoclave-treated fibers showed complete separation of cellulose fibrils, with punctures and pores on the surface. High resolution transmission electron microscope and X-ray diffraction studies suggested monoclinic unitary crystal structure. The cellulose/polypropylene composite fabrications were achieved by using injection-molding technique where the composites with 25 cellulose loading gave high tensile strength of 27 MPa, without any addition of coupling agents. Thermogravimetric analysis study showed that the thermal stability of composites was enhanced by 150 Â°C as compared to singular cellulose and polypropylene. The low water and diesel uptake suggested the compact structure of the composites. This study has developed green techniques combining heat and eco-friendly chemical treatment for cellulose extraction from agro-lignocellulosic wastes. The cellulose/polypropylene composites developed with high tensile strength, high thermal stability, and low water and diesel sorption have great potentials for conversion into eco-composite products such as polymeric material insulated cables for high voltage engineering, automotive parts, sports tools and other household or office items. Â© 2016 Elsevier Ltd.